Phytochemical and anti-inflammatory properties of Scurrula ferruginea (Jack) Danser parasitising on three different host plants elucidated by NMR-based metabolomics - Xia, Hong; Mat Isa, Nurulfiza; Fakurazi, Sharida; Ismail, Intan Safinar (John Wiley & Sons, 2020)
Introduction: Scurrula ferruginea (Jack) Danser is a hemi-parasitic shrub that is widely used as a traditional herbal medicine. Objectives: To elucidate the anti-inflammatory activity of S. ferruginea parasitising on three different hosts of Vitex negundo L., Micromelum minutum (G. Forst.) Wight & Arn. and Tecoma stans (L.) Juss ex HBK., as well as, to determine the metabolite differences related to their anti-inflammatory properties. Materials and methods: Two plant parts of S. ferruginea, stems and leaves, were extracted in water. The freeze-dried stem of S. ferruginea grown on T. stans was liquid-liquid partitioned into several solvents. Their potential anti-inflammatory activity was assessed via inhibition of nitric oxide (NO) production in lipopolysaccharide (LPS) and interferon-γ (IFN-γ)-induced RAW 264.7 macrophage cells. The metabolite variation was examined using proton nuclear magnetic resonance (1 H-NMR) combined with multivariate data analysis (MVDA). Results: Scurrula ferruginea stems parasitising on T. stans and V. negundo which were freeze dried exhibited higher anti-inflammatory activity with IC50 values of 114.47 ± 2.96 and 118.87 ± 2.31 μg/mL, respectively. The mid-polar ethyl acetate fraction of S. ferruginea hosted on T. stans displayed the highest NO inhibition with 84.80 ± 0.45% at 200 μg/mL. Principal component analysis (PCA) indicated notable and clear discriminations among the different plant parts and host plants based on the identified metabolites. Furthermore, partial least squares (PLS) regression model suggested the anti-inflammatory bioactivity might be associated with the presence of choline, isoleucine, catechin, leucine and chlorogenic acid. Conclusion: This study suggests S. ferruginea could serve as a potential anti-inflammatory agent, highlighting the importance of T. stans as the host plant.